Mycotoxin contamination in maize triggered by arthropod pests and the related protection possibilities - Horváth, Dávid (Acta Agraria Debreceniensis, 2017)
Mycotoxin contamination in harvested maize has increased in the last decades, which can be unequivocally back to the plant health troubles caused by global warming. The increasing of wounds in maize crops was occurred by climate change both on direct (hailstorm) and indirect(newly appeared pests) ways. In additional, the settling phytopathogenic microfungi on these plant wounds inflict serious human and animal health problems.The changing of Hungarian arthropod pests assemblages stand in the background of this dangerous nuisance complex. The spreading of European corn borer (Ostrinia nubilalis Hbn.) bivoltine ecotype as well as the newly appeared adventive species [cotton bollworm Helicoverpa armigera Hbn.), western corn rootworm (Diabrotica v. virgifera LeConte), fourspotted-sapbeetle (Glischrochilus quadrisignatus Say)] in Hungary can be responsible for this situation. In total, all technological elements, which obstruct the damage of these chewing mouthparts pests, as well as moderate the mechanical damage of maize, can be contribute to the reduction of both these phytopathogens injuries and mycotoxin contaminations.